THE CHAIRMAN MANAGEMENTOF PESANTREN ASSOCIATES - Ali Pirdaus Pirdaus; Ahmad Husin Ritonga Ritonga; Jalaluddin Jalaluddin (Yayasan Literasi Kita Indonesia, 2021)
This study aims to describe and analyze in depth the management of the boarding school leaders in developing the entrepreneurial spirit of the santri, starting from planning, organizing, implementing, monitoring and evaluating programs. The results of research from three Islamic boarding schools in Jambi Province regarding the management of the boarding school leadership in developing the entrepreneurial spirit of the santri found that it was in accordance with the function in management theory, namely: (1)Planning carried out by the boarding school leadership is the formulation of goals (vision, mission), entrepreneurial advice and infrastructure, planning of Ustad and Santri and curriculum. (2) Organizing: Islamic boarding school leaders share job descriptions for each pesantren program, granting authority, assigning tasks; (3) Implementation: The cultivation of life skills in Islamic boarding schools consists of two forms, namely hard skills and soft skills. Hard skills include teaching and directing entrepreneurship in the field in the form of: Plantation, agriculture, animal husbandry, pesantren cooperatives, catering, fashion, fish farming, carpentry, welding. Meanwhile, the soft skills are: organization of the students, planting foreign languages, independent students, calligraphy, IT, prayer, learning the art of reading the Koran, etc .; (4) Monitoring and Evaluation: Total quality control, visits to business premises, individual learning, evaluating the results of activities, taking clarification and correction steps, assessing and correcting all programs. The conclusion of this research is that the management of the boarding school leadership in developing the entrepreneurial spirit of the santri has been going well, with the various life skills beingtaught to make the students independent.